2021
DOI: 10.21763/tjfmpc.805231
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Cancer Awareness: Reproductive Age and Postmenopausal Women

Abstract: Objective: An important factor in the protection of women from gynecological cancers is awareness. Increasing awareness of gynecological cancer is important in terms of early diagnosis of the disease, treatment and reduction of mortality. The research was conducted to determine the gynecological cancer awareness of women of reproductive age and postmenopausal period. Methods: The study, designed as a descriptive cross-sectional type, was conducted with women who were admitted to a state hospital in Çankırı bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
(9 reference statements)
1
2
0
9
Order By: Relevance
“…20 The mean total GCAS score of the participants of this study was 156.57 ± 32.930 ( Table 3 ), which indicated high levels of gynecological cancer awareness among the women. Gözüyeşil et al 1 and Kaya Şenol et al 21 found the mean total gynecological cancer awareness score of women as 153. Another study reported the same score as 157.05 ± 21.42 for academic personnel, 150.94 ± 27.28 for administrative personnel, and 159.96 ± 24.27 for healthcare personnel.…”
Section: Discussionmentioning
confidence: 99%
“…20 The mean total GCAS score of the participants of this study was 156.57 ± 32.930 ( Table 3 ), which indicated high levels of gynecological cancer awareness among the women. Gözüyeşil et al 1 and Kaya Şenol et al 21 found the mean total gynecological cancer awareness score of women as 153. Another study reported the same score as 157.05 ± 21.42 for academic personnel, 150.94 ± 27.28 for administrative personnel, and 159.96 ± 24.27 for healthcare personnel.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Türkiye'de yapılan farklı çalışmalarda da kadınların menopoz yaşı çalışma sonuçlarımız ile benzer bulunmuştur. 20,21 Bu çalışmaya katılan kadınların %56,86'sı gelirinin giderinden düşük olduğunu belirtmiştir. Çalışmalarda kadınların büyük çoğunluğunun gelirinin giderine eşit olduğu bulunmuştur.…”
Section: Discussionunclassified
“…Literatürde jinekolojik kanser farkındalığı ve yaş ilişkisi incelendiğinde farklı sonuçlarla karşılaşılmaktadır. Bir çalışmada 50 yaş üzerindeki kadınların jinekolojik kanser farkındalık düzeyi daha düşük bulunurken, Öztürk ve arkadaşlarının çalışmasında jinekolojik farkındalık düzeyinin yaşla doğru orantılı olarak arttığı saptanmıştır 10,21. Kadın hastalıkları konusunda sağlık sorunu yaşayan, kadın hastalıkları nedeniyle düzenli kontrole giden, ailesinde kadın hastalıkları kanseri tanısı almış birey bulunan, jinekolojik kanserlerin önlenebilir olduğuna dair görüşe sahip olan kadınların jinekolojik kanser farkındalık düzeyi daha yüksek bulunmuştur.…”
unclassified
See 2 more Smart Citations